2006
DOI: 10.1038/sj.hdy.6800919
|View full text |Cite
|
Sign up to set email alerts
|

Realized correlated responses to artificial selection on pre-adult life-history traits in a butterfly

Abstract: We use artificial selection experiments targeted on egg size, development time or pupal mass within a single butterfly population followed by a common-garden experiment to explore the interactions among these life-history traits. Relationships were predicted to be negative between egg size and development time, but to be positive between development time and body size and between egg size and body size. Correlated responses to selection were in part inconsistent with these predictions. Although there was evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…Similar sexual differences in the development time and body weight were found in the common fruit fly Drosophila melanogaster [30] and the butterfly Bicyclus anynana [31]: the female pupae were heavier, but developed faster than the male ones. Small-sized pupae of the western spruce budworm Chroristoneura occidentalis also took longer to develop [32].…”
Section: Discussionmentioning
confidence: 52%
“…Similar sexual differences in the development time and body weight were found in the common fruit fly Drosophila melanogaster [30] and the butterfly Bicyclus anynana [31]: the female pupae were heavier, but developed faster than the male ones. Small-sized pupae of the western spruce budworm Chroristoneura occidentalis also took longer to develop [32].…”
Section: Discussionmentioning
confidence: 52%
“…Regardless of the explanation, these results are unexpected, as trade-off theory predicts that selection for slow development should lead to a correlated increase in body size (Roff, 2002), and potentially therefore sperm production. A previous study conducted using the same B. anynana lines, similarly reported somewhat ambiguous results; Fischer et al (2007) found that following selection for long and short development time, males from both groups had smaller pupal masses compared to control males. The effects of selection for slow development observed here could be due to a number of reasons.…”
Section: Discussionmentioning
confidence: 78%
“…Male B. anynana selected for slow development time produce fewer fertile sperm on their first mating than unselected stock males, and males selected for fast development time (values are medians ± upper and lower quartiles). development time whilst having little effect on the duration of the pupal stage (Fischer et al, 2007), so this is unlikely to be the case. Instead, the differences between males may be a by-product of differential resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Egg size can affect progeny fitness; larger offspring often mature earlier, to have improved ability to avoid or withstand predation and competition, or to have greater survival in stressful environments in comparison with smaller offspring (e.g., Azevedo et al, 1997;Fox & Czesak, 2000;Roff, 2002;Czesak & Fox, 2003;Fischer et al, 2003Fischer et al, , 2006Fischer et al, , 2007. Conversely, a female cannot increase offspring number without decreasing the size of individuals because of the presumed trade-off between number and size of offspring, which is a fundamental principle of life history theory in many taxa (e.g., Vance, 1973;Smith & Fretwell, 1974;Brockelman, 1975;McGinley et al, 1987;Sinervo 1990;Sterns, 1992;Roff, 2002).…”
Section: Discussionmentioning
confidence: 99%